Listening Skills of Class IV Students in Science Subject - Erna Yuliana; Rahman Rahman; Indra Suhendra (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Listening skills is one of the important language skills mastered by students because it can facilitate students in understanding the subject matter. Based on the results of interviews with teachers and students, data was obtained that fourth grade students at SD Cerdas Mulia Ekselensia had difficulties when listening to texts with science subject matter, with this background the study tried to help facilitate students and teachers by using one of the listening learning models. The research method used is descriptive qualitative with data collection techniques in the form of written test results, interviews and direct observation. The results of the study based on the results of the written test obtained as many as 80% of students get scores with a range of 90-100, 10% of students get grades ranging from 80-89 and 10% of students get scores with a range of 70-79